Social media addiction, maternal mental health, and children’s oral health behaviours among immigrants - Solmaz Bohlouli; Devarasa Murugeshappa; Babak Bohlouli; Maryam Amin (PLOS One, 2026)
Objectives Oral health disparities persist among immigrants. Little is known about how social media shapes the socio-psychological environment in which parenting and health behaviours occur. This study examined the link between immigrant mothers’ anxiety and depression and children’s oral health behaviours (OHBs) and evaluated social media addiction as a mediator or moderator. Methods This cross-sectional study recruited immigrant parents of children aged 2–12 years in Edmonton, Canada. Parents completed a questionnaire assessing demographics, children’s OHBs (dental visits, toothbrushing, diet), anxiety and depression (The Hospital Anxiety and Depression Scale, HADS-14; scored 0–21), and social media addiction (Bergen-6; scored 6–30). Logistic regression, mediation, and moderation analyses were performed. Results 302 questionnaires were analyzed. Mean (SD) ages of mothers and children were 37.7 (6.8) and 6.7 (3.3) years, respectively; 49% of children were female, and 65% born in Canada. On average, parents had lived in Canada for 9.9 years, and 68% had higher education. Higher maternal anxiety reduced the odds of child toothbrushing by 14% (OR: 0.86, 95% CI: 0.74 0.98), and higher depression was associated with a 21% reduction (OR: 0.79, 95% CI: 0.63–0.93). Each one-unit increase in anxiety and depression corresponded to a 49% and 51% increase in social media addiction scores (p < .05). No mediation or moderation effects were found. Conclusions Maternal anxiety and depression reduced children’s toothbrushing, with no mediation by social media addiction. Integrating mental health screening into dental care can improve oral health in immigrant communities, fostering better outcomes and inclusive policies.